Model Pelindungan Hukum Terhadap Justice Collaborator Tindak Pidana Korupsi Di Indonesia - Dwi Oktafia Ariyanti; Nita Ariyani (Jurnal Hukum IUS QUIA IUSTUM, 2020)
The issue in this research is the regulation of legal protection against justice collaborators of corruption in Indonesia which is not optimal, and the absence of an appropriate protection model for optimum efforts of protection for justice collaborators in handling corruption in Indonesia. This needs to be studied because the role of justice collaborator is very much needed to disclose major cases such as corruption, whereas his testimony can pose a large risk that must be borne by the justice collaborator, hence legal protection for justice collaborators is crucial. The method in this study uses a type of juridical normative research that is focused on studying the norms of positive law. This research concludes, first, the regulations regarding the protection of justice collaborators are listed in various regulations, but there are no specific, clear and firm regulations regarding protection and procedural arrangements for determining a justice collaborator. Thus an appropriate legal protection model is needed to optimize protection for justice collaborators in criminal acts of corruption in order to fill the legal vacuum. Second, the legal protection model for justice collaborators in handling corruption in Indonesia can utilise a persuasive protection model.